Penggunaan Enzim α-Amilase dari Saccharomycopsis fibuligera R64 untuk Peningkatan Kualitas Roti Komposit Terigu-Ubi Jalar Ungu - Agus Safari; Safri Ishmayana; Sylvi Qurrotul Aini; Saadah D. Rachman; Muhammad Yusuf; Muhammad Fadhlillah; Endah Wulandari; Idar Idar (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
Purple sweet potato (Ipomoea batatas var. Ayamurasaki) is one of typical sweet tubers which is also commonly well known as Ipomoea blackie due to blackish purple (solid purple) tuber skin and flesh. The sweet potato can be transformed into flour or pasta and used to substitute wheat flour in the production of composite bread. Instead of synthetic chemical compounds, α-amylase isolated from the yeast Saccharomycopsis fibuligera can be added to the flour or dough of the composite bread to improve its quality. The purpose of the present study was to investigate the effect of α–amylase addition on the quality of the purple sweet potato flour and pasta composite bread. The observed properties of the bread were crumbs morphology of the bread, volume increment, bread height, texture, and organoleptic test. The results showed that addition of the α-amylase to the dough of the composite bread increased the volume increment value from 155.0% to 177.1% and from 335.7% to 342.1% for the sweet potato flour and pasta bread composite, respectively. While height of the bread increased from 4.7 to 5.1 cm and from 6.9 to 7.8 cm after addition of the enzyme for the sweet potato flour and pasta bread composite, respectively. Composite bread with α-amylase addition has softer texture and higher preference. Morphology examination result showed that starch granules in the bread crums with α-amylase treatment were disrupted. Most plausibly, the enzymes degrade the starch granules and produced dextrin which inhibited the cross linking formation between starch and protein, and therefore, the speed of hardening process of the bread can be reduced.